Banning All Sugar-Sweetened Beverages in Middle Schools: Reduction of In-School Access and Purchasing but Not Overall Consumption - Taber, Daniel R. (2011)
OBJECTIVE: To determine whether state policies that regulate beverages in schools are associated with reduced in-school access and purchase of sugar-sweetened beverages (SSBs) and reduced consumption of SSBs (in and out of school) among adolescents. DESIGN: Cross-sectional. SETTING: Public schools in 40 states. PARTICIPANTS: Students sampled in fifth and eighth grades (spring 2004 and 2007, respectively). MAIN EXPOSURES: State policies that ban all SSBs and state policies that ban only soda for 2006-2007. MAIN OUTCOME MEASURES: In-school SSB access, in-school SSB purchasing behavior, and overall SSB consumption (in and out of school) in eighth grade. RESULTS: The proportions of eighth-grade students who reported in-school SSB access and purchasing were similar in states that banned only soda (66.6% and 28.9%, respectively) compared with states with no beverage policy (66.6% and 26.0%, respectively). In states that banned all SSBs, fewer students reported in-school SSB access (prevalence difference, −14.9; 95% CI, −23.6 to −6.1) or purchasing (−7.3; −11.0 to −3.5), adjusted for race/ethnicity, poverty status, locale, state obesity prevalence, and state clustering. Results were similar among students who reported access or purchasing SSBs in fifth grade compared with those who did not. Overall SSB consumption was not associated with state policy; in each policy category, approximately 85% of students reported consuming SSBs at least once in the past 7 days. Supplementary analyses indicated that overall consumption had only a modest association with in-school SSB access. CONCLUSION: State policies that ban all SSBs in middle schools appear to reduce in-school access and purchasing of SSBs but do not reduce overall consumption.